A comparative study on potentiodynamic and potentiostatic critical pitting temperature of austenitic stainless steels. Issue 1 (16th August 2017) - Sun, Y. T.; Wang, J. M.; Jiang, Y. M.; Li, J.
Abstract : Temperature and potential effect on pitting occurrence of four austenitic stainless steels in 1 M sodium chloride solution are plotted, then the influence of scan rate and chloride concentration on potentiodynamic critical pitting temperature (CPT) are investigated. Basing on the independence and reliability analysis, the potentiodynamic CPT and potentiostatic CPT are compared. To improve the reproducibility of potentiostatic CPT, an elevated potential should be applied. On the other hand, crevice corrosion induced by transpassive etching is clarified, indicating the upper limit of applied potential in potentiostatic test. Consequently, a potential of 800 or 850 mV(SCE) is recommended for austenitic stainless steels. Additionally, regression analysis is carried out to confirm the linear relationship between potentiodynamic CPT and pitting resistance equivalent. Abstract : Z curve of four austenitic stainless steels are plotted, basing on which potentiodynamic and potentiostatic critical pitting temperature (CPT) are compared. It is concluded that potentiodynamic CPT is more reliable and has a good linear relationship with PREN. On the other hand, potentiostatic CPT should be carried out with an elevated potential to improve its reproducibility.